THE IMPACT OF WATCHING ENGLISH VIDEO ON YOUTUBE IN DEVELOPING 5 YEARS OLD CHILD’S VOCABULARY ACQUISITION - Waode Surtina Jayana; Hikmawati; Intan Febriani (GLOBAL: Education Language and Humanity Journal, 2025)
This research identifies the types of vocabulary most frequently acquired by the 5 years old child through watching English videos on YouTube. A descriptive quantitative method was used as the research design. This research used observation and in-depth interviews to provide the data of child’s vocabulary acquisition. The result of this research found six categories of vocabulary. They are nouns, verbs, adjectives, adverbs, pronouns, and numbers. Numbers and nouns are the most frequently acquired by the child. Moreover, the data indicates that receptive vocabulary is the most frequently acquired by the child than in productive vocabulary. The child can recognize the words easily than produce the word, for example, the child can point to the picture of the words, but the child found it difficult to produce the words verbally.